2014
DOI: 10.1371/journal.pone.0096651
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Metabolic Syndrome by Non-Alcoholic Fatty Liver Disease in Northern Urban Han Chinese Population: A Prospective Cohort Study

Abstract: ObjectivesTo explore the relationship between non-alcoholic fatty liver disease (NAFLD) and the metabolic syndrome (MetS), and evaluate the value of NAFLD as a marker for predicting the risk of MetS in a large scale prospective cohort from northern urban Han Chinese population.Materials and MethodsA total of 17,920 MetS-free at baseline cohort members was included in the current study between 2005 and 2011. The baseline characteristics of the cohort were compared by NAFLD status at baseline, MetS status after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
(54 reference statements)
2
23
1
1
Order By: Relevance
“…In an adjusted model for confounding factors, such as age, metabolic factors, smoke and exercise, the Hazard Ratios [HRs (95 % CIs)] of NAFLD for predicting MS are 2.06 (1.72, 2.46) and 1.55 (1.39, 1.72) in female and male populations, respectively. The authors conclude that NAFLD is an independent risk factor for predicting the risk of MS, and the patients with NAFLD should initiate weight and dietary control to prevent the occurrence of MS [33]. This finding corroborates the central role of insulin resistance in the pathogenesis of MS, enhanced by the coexistence of fatty liver [34].…”
Section: Nalfd: the Liver At The Centersupporting
confidence: 55%
“…In an adjusted model for confounding factors, such as age, metabolic factors, smoke and exercise, the Hazard Ratios [HRs (95 % CIs)] of NAFLD for predicting MS are 2.06 (1.72, 2.46) and 1.55 (1.39, 1.72) in female and male populations, respectively. The authors conclude that NAFLD is an independent risk factor for predicting the risk of MS, and the patients with NAFLD should initiate weight and dietary control to prevent the occurrence of MS [33]. This finding corroborates the central role of insulin resistance in the pathogenesis of MS, enhanced by the coexistence of fatty liver [34].…”
Section: Nalfd: the Liver At The Centersupporting
confidence: 55%
“…Prospective studies examining the association between NAFLD and the risk of incident T2D are summarized in Supporting information Table S1, while those examining the association between NAFLD and the risk of incident MetS are reported in Supporting information Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 20 prospective cohort studies were retrieved, 12 of which were excluded from analysis based on the exclusion criteria of the study . Overall, eight cohort studies (five community‐based and three population‐based) were identified and included in the meta‐analysis (as schematically summarized in Fig. , Panel B).…”
Section: Resultsmentioning
confidence: 99%
“…Few prospective studies have indicated that NAFLD can predict a higher incidence of MetS515253. A recent meta-analysis of prospective studies has demonstrated that NAFLD is associated with a nearly two-fold increased in the incident risk of type 2 diabetes and MetS.…”
Section: Discussionmentioning
confidence: 99%